Cities Full of Symbols A Theory of Urban Space and Culture (2011)
This book examines design proposals that show symbolic handling of the 9/11 attack on New York, the disaster symbolism of the ship washed ashore by the tsunami in Banda Aceh, and the design of the symbol of the city of Cape Town derived from a remnant of Dutch colonial architecture, or the mass pilgrimage to Elvis’s Graceland in Memphis. Cities Full of Symbols develops urban symbolic ecology and hypercity approaches into a new perspective on social cohesion. Approaches of architects, anthropologists, sociologists, social geographers and historians converge to make this a book for anyone interested in urban life, policymaking and city branding.